In vitro biological activity of three marine sponges from theonella and haliclona genera collected from Bidong Island, Terengganu, Malaysia - Nur Amira Jamaludin; Kamariah Bakar; Jasnizat Saidin (Penerbit Universiti Kebangsaan Malaysia, 2023)
Marine sponges are primitive sessile animals that are rich sources of biologically active compounds. This paper aimed to assess the in-vitro biological activity of marine sponges from Theonella and Haliclona genera collected from Bidong Island, Terengganu, Malaysia. Biological activities such as antibacterial (discs diffusion assay), antioxidant (DPPH free-radical scavenging assay), and cytotoxicity activity (against cancerous HeLa, MCF-7, HepG-2 cell lines and the normal cell line Vero) were evaluated using MTT cytotoxicity assay. The bioassays were done on methanol extracts at different concentrations. Results indicate that T. swinhoei, and T. cf cupola showed low antibacterial capabilities ranging from 0 to 50 mg/mL and exhibited medium antioxidant activity with the IC50 value of 23.25 ± 1.57 and 18.52 ± 0.86 mg/mL, respectively. Cytotoxicity activities indicate that both species of T. swinhoei and T. cf cupola possesses toxic capabilities to inhibit the proliferation of all cancer cell lines used and demonstrated no significant toxicity for the normal cell line used in this study. Haliclona fascigera showed medium antibacterial activity against all Gram-positive bacteria and low activity against Gram-negative bacteria used. Haliclona fascigera exhibited antioxidant activity with an IC50 value of 1.80 ± 0.08 mg/mL and outcomes of the cytotoxicity activity assay against all cancer cells showed IC50 below 30 µg/mL. Marine sponges evaluated in this study indicate promising bioactive compounds that can be an excellent candidate for drug discovery in prospecting novel antibiotics and anticancer. Despite showing low antibacterial and medium antioxidant activity, species from both Theonella can be further studied in other assays to explore other biological activities whilst marine sponge H. fascigera possesses excellent capabilities in antibacterial, antioxidant, and cytotoxicity activities that can be further studied its chemical compositions for future research.